People’s Response to Disasters in the Philippines - Gaillard, J. author. aut Link
XX, 193 p.
Keywords: This book provides a critical perspective on people's response to disasters in the Philippines. It draws upon an array of case studies to discuss people's vulnerability, capacities and resilience in facing a wide range of different hazards.